CALORIMETRIC TECHNIQUE OF DETERMINING THE COMBUSTION HEAT OF FUELS FROM SOLID MUNICIPAL WASTE - Скляренко, Євген; Воробйов, Леонід (Modern engineering and innovative technologies, 2023)
The issues of disposal of solid municipal waste with the production of new fuels based on them are considered, and the technology of their production with predetermined heat-technical characteristics, in particular, their heat of combustion, is proposed.